One-dimensional electron lattice system with a long-range interelectron repulsion on a disordered host lattice - Slutskin, A.A.; Kovtun, H.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
We study what happens to generalized Wigner crystal, GWC (a regular structure formed by narrow-band electrons on a one-dimensional periodic host lattice), when there is a host lattice random distortion that does not break the host-lattice long-range order. We show that an arbitrarily weak distortion of the kind gives rise to soliton-like GWC defects (discrete solitons, DS) in the ground state, and thereby converts the ordered GWC into a new disordered macroscopic state — lattice Wigner glass (LWG). The ground-state DS concentration is found to be proportional to l4 (l is the typical host-lattice strain). We show that the low-temperature LWG thermodynamics and kinetics are fully described in DS terms. A new phenomenon of a super-slow logarithmic relaxation in the LWG is revealed. Its time turns out to be tens orders of magnitude greater than the microscopic ones. Analytical dependences of LWG thermodynamic quantities on temperature and l are obtained for an arbitrary relationship between the relevant Coulomb energies and the electron bandwidth.